(untitled) - Piper, Don; (1950-...) (U.S.A, 2004)
In the ten years since (3z(B90 Minutes in Heaven(3y (Bwas published, millions of people worldwide have read the incredible true story of Don Piper's experience with death and life--and in reading they have found their own lives changed.After a semi-truck collided with Don Piper's car, he was pronounced dead at the scene. For the next ninety minutes, he experienced the glories of heaven. Back on earth, a passing minister felt led to stop and pray for the accident victim even though he was told Piper was dead. Miraculously, Piper came back to life, and the pleasure of heaven was replaced by a long and painful recovery.With a personal update from Don on the impact the book has had on him, his family, and the millions who have heard his story, even those who have read the original book will want to be part of the continuing story of (3z(B90 Minutes in Heaven(3y (Bwith this new edition.s
Keywords: Piper, Don -- 1950-